2019
DOI: 10.3390/ani9121006
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Fatty Acids in Ruminal Fluid Can Be Used to Predict Methane Yield of Dairy Cows

Abstract: The dry matter intake (DMI) of forage-fed cattle can be used to predict their methane emissions. However, many cattle are fed concentrate-rich diets that decrease their methane yield. A range of equations predicting methane yield exist, but most use information that is generally unavailable when animals are fed in groups or grazing. The aim of this research was to develop equations based on proportions of ruminal volatile-fatty-acids to predict methane yield of dairy cows fed forage-dominant as well as concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 68 publications
2
33
0
1
Order By: Relevance
“…However, methane may be isolated from this problem because it is strongly related to the breakdown of feed and the digestive capabilities of the animal, rather than the focus of energy partitioning to a specific output. More recently, Williams et al (2019) showed that VFA proportions in ruminal fluid can be used to predict methane yield, and they suggested that their approach is among the cheapest methods for estimating methane yield of dairy cows. Thus, proxy methane phenotypes related to RMP may be able to be estimated.…”
Section: Challenges Of Small Data Setsmentioning
confidence: 99%
“…However, methane may be isolated from this problem because it is strongly related to the breakdown of feed and the digestive capabilities of the animal, rather than the focus of energy partitioning to a specific output. More recently, Williams et al (2019) showed that VFA proportions in ruminal fluid can be used to predict methane yield, and they suggested that their approach is among the cheapest methods for estimating methane yield of dairy cows. Thus, proxy methane phenotypes related to RMP may be able to be estimated.…”
Section: Challenges Of Small Data Setsmentioning
confidence: 99%
“…Importantly, one limitation of our study is that we estimated methane production using volatile fatty acid stichometry rather than directly measuring it. Using volatile fatty acid stichometry to estimate methane production has been widely used in previous studies because of the strong relationship between rumen fermentation parameters and methane (Cabezas-Garcia et al, 2017;Williams et al, 2019;De Souza et al, 2020). It is important to recognize uncertainty and variability in methane across different methods (Hristov et al, 2018); however, the method used still is feasible to compare differences across treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Two 50-mL samples of ruminal fluid were then preserved by the addition of 1.0 mL of 50% H 2 SO 4 and stored at −20 • C. Ruminal fluid samples were thawed at room temperature and centrifuged (15,000 × g, 4 • C, 30 min), and the supernatant was analyzed for volatile fatty acids by gas chromatography (Erwin et al, 1961) and ammoniacal nitrogen by the phenol-hypochlorite procedure (Chaney and Marbach, 1962). Methane was calculated using volatile fatty acid stoichiometry as previously reported (De Souza et al, 2020) according to the equations proposed by Williams et al (2019).…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…However, due to the limited sampling times used in these latter methods [ 5 ], and the marked diurnal patterns in the magnitude of MeP from dairy cows [ 6 ], some researchers have questioned the suitability of these recent methods for quantifying daily MeP of individual cows [ 7 , 8 ]. Proxy methods for estimating daily MeP or MeY of individual animals are numerous, including predictions based on dry matter intake (DMI) [ 9 ], feed composition [ 10 ], methane to carbon dioxide ratio in breath [ 11 ], milk fatty acids [ 12 ], and volatile fatty acids in ruminal fluid [ 13 ]. However, proxy methods have generally had poor predictive accuracy and therefore have limited applicability in terms of predicting MeP from individual animals [ 14 ].…”
Section: Introductionmentioning
confidence: 99%